Not a Popularity Contest : Bringing Rigor to Open Governments - Fiszbein, Ariel (2012)
Participation, dialogue, openness. These are values we cherish and aspire to. Who would be in favor of unilateralism, monologue, or isolation as guiding principles of development? The call for open development as a multipolar and more democratic search for solutions is almost a platitude. The issue is not whether openness, a positive attribute in itself, can promote better policies, but rather what are the conditions required for openness to succeed.